2013
DOI: 10.1002/poc.3260
|View full text |Cite
|
Sign up to set email alerts
|

Laplacian of the electron density: a hole–lump interaction as a tool to study stereoelectronic control of chemical reactions

Abstract: a In this work, we applied the theory of Atoms in Molecules to the study of carbocationic transition states involved in two different reaction mechanisms, using the proposed mechanism of ethylene dimerization over Brønsted-acid site of zeolite catalyst as a study case. We report the main results of the analysis of the Laplacian of electron density distribution and Bader's atomic charges to increase our understanding of stereoelectronic aspects of these chemical reactions. At B3LYP/6-31++G(d,p)//B3LYP/6-3G(d,p)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…MEPs based on electron density provide valuable information about the shape, volume, and electronic properties of are also observed the catalytic system, and it have been previously used in heterogeneous catalysis in order to predict interactions between the adsorbate and the catalyst [26,27]. Also, previous studies of reactions on zeolites showed that the stabilization and formation of intermediates and transition states, depend on the availability of electrons on the surface and the electronic availability plays a crucial role to stabilize the formed species [23,28,29].…”
Section: Model Of [Cta + ]-Si-mcm-41 Catalyst (Non-calcined Catalyst) or Ion-pair Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…MEPs based on electron density provide valuable information about the shape, volume, and electronic properties of are also observed the catalytic system, and it have been previously used in heterogeneous catalysis in order to predict interactions between the adsorbate and the catalyst [26,27]. Also, previous studies of reactions on zeolites showed that the stabilization and formation of intermediates and transition states, depend on the availability of electrons on the surface and the electronic availability plays a crucial role to stabilize the formed species [23,28,29].…”
Section: Model Of [Cta + ]-Si-mcm-41 Catalyst (Non-calcined Catalyst) or Ion-pair Modelmentioning
confidence: 99%
“…Kubota et al reported that the high activity of Si-MCM-41 with a quaternary ammonium ion occluded emerges only when both parts form a composite [4]. Martins and co-workers studied the Knoevenagel condensation reaction using Si-MCM-41 molecular sieves as basic catalyst, where the pores were occluded by the SDA, and suggested from 29 Si NMR spectroscopy and O1s XPS measurements, that the active site is the ≡SiO − CTA + ionic pair, which is the basic site itself, also they suggested that the reaction should occur in the pore mouth [5]. Other work showed that different mesoporous materials synthesized with surfactants of different lengths in the carbon chain ensure greater catalytic activity when the occluded cation is more voluminous, this was attributed to the more weaker interaction with SiO − sites, thus increasing the SiO − basicity [9].…”
Section: Introductionmentioning
confidence: 99%